Pathogenesis and clinical presentation of rosacea as a key for a symptom‐oriented therapy. (December 2016) - Reinholz, M; Ruzicka, T; Steinhoff, M; Schaller, M; Gieler, U; Schöfer, H; Homey, B; Lehmann, P; Luger, TA
Summary: Rosacea is a common chronic inflammatory skin disorder that typically occurs in adults and affects the face. Synonyms of rosacea include "acne rosacea", "couperose" and "facial erythrosis", in German also "Kupferfinne" and "Rotfinne". The disorder is characterised by a chronic and flaring course and is caused by a genetically predisposed, multifactorial process. A higher incidence is seen in people with fair skin and a positive family history. The characteristic rosacea symptoms manifest primarily, but not exclusively centrofacially, with forehead, nose, chin and cheeks significantly affected. Based on the various main symptoms a classification of the individual clinical pictures can be performed. However, a classification often does not reflect the clinical reality, since the various symptoms commonly coexist. The present review provides an introduction on pathogenesis and clinical manifestations of rosacea and prefers a symptom‐oriented therapy approach.